Oxidative radical cyclisations for the synthesis of gamma-lactones. - Powell, L; Docherty, P; Hulcoop, D; Kemmitt, P; Burton, J (2008)
The use of manganese(III) acetate in combination with copper(II) triflate allows the synthesis of [3.3.0]-bicyclic gamma-lactones from 4-pentenylmalonates in excellent yields.